A Jewish Paul the Messiah's herald to the gentiles - Thiessen, Matthew 1977- (Grand Rapids, Michigan Baker Academic, 2023)
"A highly respected New Testament scholar offers an accessible introduction to Paul that clearly situates him within first century Judaism"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Theology; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Christianity and other religions -- Judaism; Judaism -- Relations -- Christianity